2006
DOI: 10.1055/s-2005-865847
|View full text |Cite
|
Sign up to set email alerts
|

Chronic L-Arginine Supplementation Enhances Endurance Exercise Tolerance in Heart Failure Patients

Abstract: The purpose of the study was to determine the potential beneficial effect of six weeks oral L-arginine supplementation (LAS) on endurance exercise, an important determinant of daily-life activity in patients with chronic stable heart failure (CHF). After an initial incremental maximal exercise test, CHF patients performed an identical thirty-minute interval endurance exercise test before and after six weeks with (L-arginine group; ARG) or without LAS (control group; CTL). Hemodynamic, respiratory, and metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…An L-arginine-related HR decrease was described in healthy and in heart-failure patients (42). The mechanisms involved remain unclear, but a direct or indirect increase in parasympathetic activity might play a key role (42,43). Such a hypothesis might well apply in cardiac-denervated HTx patients because the cardiac hormone atrial natriuretic peptide may have a cardiac-sympathoinhibitory effect in patients after an HTx (44).…”
Section: Effect Of Chronic Lasmentioning
confidence: 95%
See 1 more Smart Citation
“…An L-arginine-related HR decrease was described in healthy and in heart-failure patients (42). The mechanisms involved remain unclear, but a direct or indirect increase in parasympathetic activity might play a key role (42,43). Such a hypothesis might well apply in cardiac-denervated HTx patients because the cardiac hormone atrial natriuretic peptide may have a cardiac-sympathoinhibitory effect in patients after an HTx (44).…”
Section: Effect Of Chronic Lasmentioning
confidence: 95%
“…LAS significantly decreased the resting HRs of our patients, and this may theoretically improve their exercise capacity by reversing the chronotropic insufficiency of an HTx. An L-arginine-related HR decrease was described in healthy and in heart-failure patients (42). The mechanisms involved remain unclear, but a direct or indirect increase in parasympathetic activity might play a key role (42,43).…”
Section: Effect Of Chronic Lasmentioning
confidence: 98%
“…The impairment of NO production and the resulting endothelial dysfunction are the major factors that limit exercise capacity in patients with various cardiopulmonary conditions. As the result, arginine supplementation has been shown to improve exercise capacity in patients with hypercholesterolemia [9], chronic heart failure [10][11][12], pulmonary hypertension [13] and stable angina pectoris [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A randomized, double-blind trial found six weeks of arginine supplementation (5.6-12.6 g per day) significantly improved blood flow, arterial compliance, and functional status of HF patients compared to placebo [123]. In the study of Doureleau et al, HF subjects obtained significant improvement of the performance at exercise test after supplementation with arginine: mean heart rate decreased throughout exercise and recovery while systemic blood pressure and respiratory parameters remained unchanged [124]. Moreover, exercise-induced peak increase in plasma lactate, also was blunted in subjects taking arginine.…”
Section: Iia Argininementioning
confidence: 90%